2010
DOI: 10.3109/00365511003650165
|View full text |Cite
|
Sign up to set email alerts
|

Relation of coffee consumption and serum liver enzymes in Japanese men and women with reference to effect modification of alcohol use and body mass index

Abstract: Coffee drinking probably confers protection against alcohol-related increase in liver enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
5
23
0
2
Order By: Relevance
“…Coffee consumption was inversely related with serum level of liver enzymes in the study including Japanese men and women (Ikeda et al, 2010). In the current study, alcohol consumption showed a nonsignificant association with ALT similar to the study performed in Japan (Nakamura et al, 1998;Nakamura et al, 1980).…”
Section: Resultssupporting
confidence: 72%
“…Coffee consumption was inversely related with serum level of liver enzymes in the study including Japanese men and women (Ikeda et al, 2010). In the current study, alcohol consumption showed a nonsignificant association with ALT similar to the study performed in Japan (Nakamura et al, 1998;Nakamura et al, 1980).…”
Section: Resultssupporting
confidence: 72%
“…11,18-20 Some fairly large populationbased studies suggested that coffee drinking inhibited AST and ALT activities in Japan, Italy, and the United States. 8,11,21 AST and ALT are used as markers of liver inflammation. Abnormally elevated serum aminotransferase levels result from heterogeneous causes such as viral infection, drug toxicity, obesity, and excessive alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the alcohol-related rise in aminotransferases was attenuated with coffee drinking in a Japanese study. 11 Until now, there have been limited numbers of Asian studies on coffee and liver function tests. Liver functions tests are indicators of hepatocellular health.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis involves the observation that coffee consumption is associated with better lifestyle choices, confounding the positive effects that had been associated with coffee consumption. One previously discussed cohort study argues against this hypothesis, demonstrating subjects that were prone to increased coffee consumption actually had higher median consumption of cigarettes, lower education levels, and higher median intake of alcohol than those with decreased coffee consumption[16]. …”
Section: Discussionmentioning
confidence: 99%
“…A 2010 study in Japan evaluated levels of AST, ALT, and GGT amongst various subgroups of men and women with high BMI, low BMI, and high and low alcohol consumption. Transaminases were noted to be lower amongst men and women with higher coffee consumption, the relationship appearing to be stronger in those with higher alcohol consumption and lower BMI[16]. …”
Section: Coffee and An Association With Decreased Liver Enzymesmentioning
confidence: 99%